MiR-127 and miR-376a act as tumor suppressors by in vivo targeting of COA1 and PDIA6 in giant cell tumor of bone. (28th November 2017) - Herr, Ingrid; Sähr, Heiner; Zhao, Zhefu; Yin, Libo; Omlor, Georg; Lehner, Burkhard; Fellenberg, Jörg
Abstract: Giant cell tumors of bone (GCTB) are generally benign bone tumors associated with expansive osteolytic defects, a high rate of recurrence and potential malignant transformation. We recently observed silencing of miR-127-3p and miR-376a-3p in GCTB and identified COA1 and PDIA6 as their target genes. Here, we investigate the impact of these microRNAs and their target genes on tumor engraftment and progression of giant cell tumor stromal cells (GCTSC) in vivo by xenotransplantation on the chorioallantoic membrane of chicken eggs. Prior to transplantation, the neoplastic GCTSCs were transfected with miRNA mimics or siRNAs directed against their target genes. Restoration of miR-127-3p and miR-376a-3p reduced the tumor take rate to 17% and 47% compared to 95% in the controls. The tumor volumes were significantly reduced to 29% by both miRNAs. Silencing of COA1 and PDIA6 significantly decreased the tumor volumes to 37.7% and 42.7%, while the tumor take rates remained stable. Our results indicate that re-expression of miR-127-3p and miR-376a-3p induces a strong tumor suppressor effect in GCTSC, which is partially mediated via COA1 and PDIA6 . Highlights: Giant cell tumor stromal cells graft on the CAM of chicken eggs. Mir-127 and miR-376a act as tumor suppressors in vivo . Restoration of miR-127 and miR-376a reduce tumor growth. Silencing of the target genes COA1 and PDIA6 reduces tumor growth.